Clinical and Socioeconomic Predictors of Mortality in Penetrating Abdominal Trauma: A Retrospective Analysis From a Nigerian Tertiary Hospital (Western Journal of Medical and Biomedical Sciences, 2025)
Penetrating abdominal trauma (PAT) remains a life-threatening surgical emergency in low-resource settings, where delays in care and limited surgical infrastructure amplify mortality risks. This retrospective study analyzed 43 PATcases managed at Alex Ekwueme Federal University Teaching Hospital, Abakaliki, Nigeria, from January 2022 to December 2023, to identify predictors of mortality and evaluate outcomes. Data on demographics, injury mechanisms, clinical  presentation, surgical timing, and outcomes were extracted from medical records. The cohort predominantly comprised young males (n=38, 88.4%) aged 19–44 years (n=29, 67.4%), with gunshot wounds (n=38, 88.4%) and machete injuries (n=7, 16.3%) as leading mechanisms. Over 79.1% (n=34) underwent surgery >24 hours post-injury, often due to delayed referrals and lack of prehospital care. Overall mortality was 25.6% (n=11), with hemorrhagic shock (SBP
Keywords: Haemorrhagic shock; Low-resource setting; Mortality predictors; Nigeria; Penetrating abdominal trauma; Surgical delay